Short, Intermediate and Long Term Follow up of Device Closure of Atrial Septal Defect (Secundum) Cases: Thirteen Years Experience with Special Reference to Complications (Cardiovascular Journal, 2015)
Background: Device closure of Atrial Septal Defect (ASD) Secundum type is gaining popularity because of short learning curve, cosmetic benefits, reduced hospital stay, reduced working hour loss, reduced pain, less or no need for general anesthesia etc. In most centers this is the first choice of therapy comparing to surgical closure. The major concern recently is related to development of erosion and aortic regurgitation. Objective of our study is to review the outcome of our cases over last 13 years with special reference to complication in our series and review from literatures. Methods: One thousand and twenty patients with secundum ASD with indication for closure, age 8 months to (median 11 years) 68 years from December 2000 to December 2013 were included in the study. Patient were followed up after device closure at 1, 3, 6, 9, 12, and 18 months and yearly thereafter with ECG, CXR, and Echocardiography. One hundred and seventy two cases were lost from follow up after first year. Results: Device was implanted on 1020 patient but tried on 1075 patient. Forty one cases postponed after balloon sizing and 12 for unstable position of device or mashrooming deformity of device. Immediate complications were ST changes (n=12), transient arrhythmia (n=4), residual shunt (n=7) etc. Immediate major complication was embolization of device (n=2). There was no late embolization, thromboembolic events, erosion, pericardial effusion, aortic regurgitation in follow up. Mean follow up time was 6.9 years (8 month to 13 years). Residual shunt was abolished in all patients other than those having another uncovered ASD (2 cases). Conclusion: Device closure of ASD is safe and effective in short, intermediate and long term follow up without any major late complication. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22248 Cardiovasc. j. 2015; 7(2): 85-92